2017
DOI: 10.1007/s10753-017-0650-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Houttuyfonate on Pulmonary Inflammation in COPD Model Rats

Abstract: The anti-inflammatory effect of sodium houttuyfonate (SH), an herbal-originated drug that used in China clinically, was investigated on chronic obstructive pulmonary disease (COPD) inflammatory model rats induced by combination usage of cigarette smoke (CS) and lipopolysaccharide (LPS). The morphology of the lung tissue, the expression levels of cytokines in the bronchoalveolar lavage fluid (BALF), the protein levels of TLR4, NF-κB p65, and SIGIRR, and the mRNA levels of TLR4, MyD88, NF-κB p65, and SIGIRR in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…H. cordata is a classical Chinese herb used in traditional Chinese medicine for inflammatory diseases, such as pneumonia. Recently, SH, which was a pure compound extracted from H. cordata , has been found exerting anti-inflammatory and anti-fibrotic effects on animal and cell models of various diseases ( Gao et al, 2010 ; Du et al, 2012 ; Kang and Koppula, 2014a , 2015 ; Xu et al, 2015 ; Zhu et al, 2015 ; Wu et al, 2017 ). On LPS-induced bovine endometrial epithelial cell inflammation, SH treatment significantly decreased the expression of pro-inflammatory cytokines and alleviated the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. cordata is a classical Chinese herb used in traditional Chinese medicine for inflammatory diseases, such as pneumonia. Recently, SH, which was a pure compound extracted from H. cordata , has been found exerting anti-inflammatory and anti-fibrotic effects on animal and cell models of various diseases ( Gao et al, 2010 ; Du et al, 2012 ; Kang and Koppula, 2014a , 2015 ; Xu et al, 2015 ; Zhu et al, 2015 ; Wu et al, 2017 ). On LPS-induced bovine endometrial epithelial cell inflammation, SH treatment significantly decreased the expression of pro-inflammatory cytokines and alleviated the inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
“…Sodium Houttuyfonate (SH), which was a pure compound extracted from a Chinese herb Houttuynia cordata , has shown potent anti-inflammatory and anti-fibrotic activities on various animal and cell models of diseases, like lipopolysaccharide (LPS)-induced acute lung injury (ALI), LPS-induced bovine endometrial epithelial cell inflammation, smoking-induced chronic obstructive pulmonary disease (COPD), ventricular remodeling induced by abdominal aortic banding and so on ( Gao et al, 2010 ; Du et al, 2012 ; Kang and Koppula, 2014a , 2015 ; Xu et al, 2015 ; Zhu et al, 2015 ; Wu et al, 2017 ). Based on these findings, we doubted whether SH with an inherent anti-inflammatory and anti-fibrotic potency, could ameliorate post-infarct cardiac remodeling and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium houttuyfonate (SH) ( Fig. 1) is one of the main compounds in the volatile oil of Houttuynia cordata Thunb., which has been used as an anti-pyretic and detoxicated herbal medicine for the therapy of infections for an extensive period of time (15,16). The effects of SH on diabetic nephropathy and glomerulonephritis have been reported in experimental animals (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies highlight the role of TLR4/NF-κB signaling in the in ammatory lung diseases, such as asthma and COPD [28,29]. We found that exposure to CSE signi cantly induced the activation of TLR4/NF-κB signaling pathway in 16HBE cells.…”
Section: Discussionmentioning
confidence: 60%